2015
DOI: 10.1007/s00128-015-1668-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia on the Physiology of Zebrafish (Danio rerio): Initial Responses, Acclimation and Recovery

Abstract: Hypoxia often occurs in aquatic environments as dissolved oxygen (DO) concentration decrease to a level where it is detrimental to aquatic organisms. To investigate the effects of hypoxia on the physiology of zebrafishes (Danio rerio), the organisms were kept at normoxic conditions (DO: 8 ± 0.3 mg L(-1): control group) or were subjected to mild (DO: 3 ± 0.3 mg L(-1)) or severe hypoxia (DO: 1 ± 0.2 mg L(-1)) for 48 h and a subsequent restoration of oxygen concentrations (DO: 8 ± 0.3 mg L(-1)) for another 96 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…(D) As ambient P O2 declines, Ṁ O2 first decreases with a more or less constant slope, and then transitions to a much sharper slope of declinee.g. crucian carp (Nilsson, 1992), zebrafish (Feng et al, 2016), branquinha (Johannsson et al, 2018).…”
Section: Calculation Of P Crit Usually Involves Selective Data Editingmentioning
confidence: 99%
“…(D) As ambient P O2 declines, Ṁ O2 first decreases with a more or less constant slope, and then transitions to a much sharper slope of declinee.g. crucian carp (Nilsson, 1992), zebrafish (Feng et al, 2016), branquinha (Johannsson et al, 2018).…”
Section: Calculation Of P Crit Usually Involves Selective Data Editingmentioning
confidence: 99%
“…Herein we added new studies and species not reported in the previous publication (Moreira et al, 2016 ). The 14 species added in this study are Astronotus ocellatus (Marcon, 1996 ); Bunodosoma cangicum (Abujamara et al, 2014 ); Catla catla (Singh et al, 2016 ); Colossoma macropomum (Marcon, 1996 ); Crepipatella dilatata (Cubillos et al, 2016 ); Danio rerio (Feng et al, 2016 ); Larimichthys crocea (Wang et al, 2017 ); Neohelice granulata ((Geihs et al, 2016 ); Pandalus borealis (Dupont-Prinet et al, 2013 ; Pillet et al, 2016 ); Pelteobagrus fulvidraco (Yang et al, 2014 ); Pelteobagrus vachelli (Zhang et al, 2016 ); Plectus murrayi (Adhikari et al, 2009 ); Reinhardtius hippoglossoides (Pillet et al, 2016 ); Scapharca inaequivalvis (Foschi et al, 2012 ). (C) Illustrative topological drawing of metazoan radiation for 10 animal lineages (Erwin et al, 2011 ; Erwin, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish were Journal of Fish Health Vol. 3 (2) -Dec 2023 https://doi.org/10.29303/jfh.v3i2.3249 exposed to four different levels of tolerable DO namely, three hypoxic levels (20%-30% of O2 saturation, 40%-50% of O2 saturation, 60%-70% of O2 saturation) and one normoxic level (80% and above of O2 saturation) (Feng et al, 2015) under four different experimental setups (each setup, n=30). The DO levels were regulated using nitrogen gas (25ml gas per sec) by following the methods of Butlet et al (1994).…”
Section: Stress Exposure To Zebrafishmentioning
confidence: 99%
“…It was also analysed that the fish showed behavioural distress at lethal levels of pH (Zahangir et al, 2015). The physiology of zebrafish gets highly affected when exposed to lower than tolerable range of oxygen in both adults and embryos (Feng et al, 2015;Lin et al, 2020). Fishes like Tor putitora, bonefish and Oreochromis niloticus showed behavioural fluctuations when exposed to hypoxic conditions (Xu et al, 2006;Shultz et al, 2011;Kalkhundiya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%